1983
DOI: 10.1093/oxfordjournals.aje.a113632
|View full text |Cite
|
Sign up to set email alerts
|

Associations Among Cataract Prevalence, Sunlight Hours, and Altitude in the Himalayas1

Abstract: The relationship between cataract prevalence, altitude, and sunlight hours was investigated in a large national probability sample survey of 105 sites in the Himalayan kingdom of Nepal, December 1980 through April 1981. Cataract of senile or unknown etiology was diagnosed by ophthalmologists in 873 of 30,565 full-time life-long residents of survey sites. Simultaneously, the altitude of sites was measured using a standard mountain altimeter. Seasonally adjusted average daily duration of sunlight exposure for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(73 citation statements)
references
References 0 publications
2
69
0
2
Order By: Relevance
“…Lens opacification has been linked to ocular exposure to UV radiation particularly UV B. 42 Few authors 43,44 found a positive correlation between cataract prevalence and duration of sunlight exposure. In the present study, PSC followed by nuclear cataract was documented in patients experiencing occupational exposure to sunlight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lens opacification has been linked to ocular exposure to UV radiation particularly UV B. 42 Few authors 43,44 found a positive correlation between cataract prevalence and duration of sunlight exposure. In the present study, PSC followed by nuclear cataract was documented in patients experiencing occupational exposure to sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Cataract has a multifactorial aetiology with genetic, 1 sociodemographic, 2 behavioral, and environmental factors 3,4 all being implicated. Although it is likely that these factors interact with each other, age is still the single most important risk factor for cataract.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend of increased prevalence of nontrachomatous corneal opacity compared to trachomatous corneal opacity has also been demonstrated in other developing countries. [5][6][7] Non-trachomatous corneal opacity therefore warrants close attention from national eye care planners seeking to reverse this trend. Previous data concerning this type of disease in African populations are few.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Equipment such as slit lamps have been used, as well as more basic equipment such as torches, and  2.5 loupes. 8,14 The availability of an accurate and cheap screening tool that could be easily used by non-ophthalmologists would potentially be of great use in cataract detection.…”
Section: Discussionmentioning
confidence: 99%